1997
DOI: 10.1002/(sici)1096-9861(19970106)377:1<15::aid-cne3>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions and density of dendritic spines from rat dentate granule cells based on reconstructions from serial electron micrographs

Abstract: In the hippocampus, most excitatory synapses are located on dendritic spines. It has been postulated that the geometry of spines and/or postsynaptic density (PSD) influences synaptic efficiency and may contribute to the expression of plastic processes such as learning or long-term potentiation (LTP). Based on three-dimensional reconstructions of dentate granule cell dendrites from serial electron micrographs, we have measured head dimensions, neck cross-sectional areas, neck length, and PSD area and form of 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
52
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 65 publications
10
52
0
Order By: Relevance
“…In addition, DIP spines have significantly longer PSDs and a higher percentage of perforated synapses than DIN spines. PSD length is known to correlate with spine size (Trommald and Hulleberg, 1997;Toni et al, 2001;Meng et al, 2002;Fujisawa et al, 2006), and perforated synapses are larger than those of nonperforated (simple) synapses (Calverley and Jones, 1990;Jones and Harris, 1995;Muller, 1997;Toni et al, 2001). Our results are the first to show that larger spine head areas, longer PSDs, and perforated PSDs are associated with another characteristic, abundance of drebrin A.…”
Section: Discussionsupporting
confidence: 57%
“…In addition, DIP spines have significantly longer PSDs and a higher percentage of perforated synapses than DIN spines. PSD length is known to correlate with spine size (Trommald and Hulleberg, 1997;Toni et al, 2001;Meng et al, 2002;Fujisawa et al, 2006), and perforated synapses are larger than those of nonperforated (simple) synapses (Calverley and Jones, 1990;Jones and Harris, 1995;Muller, 1997;Toni et al, 2001). Our results are the first to show that larger spine head areas, longer PSDs, and perforated PSDs are associated with another characteristic, abundance of drebrin A.…”
Section: Discussionsupporting
confidence: 57%
“…Notably, our study indicates that stubby spines are greatly over-reported in the light-microscopic literature, due to insufficient optical resolution. This conclusion is supported by electron microscopy studies that typically observe only low fractions (a few percent) of stubby spines in adult tissue 24,25,38,43 . This is not merely a semantic issue because spines with large heads and thin and short necks (e.g.…”
mentioning
confidence: 67%
“…Electron microscopy studies have provided exquisitely detailed and quantitative analyses of spine morphology in fixed samples 24,38,39 , but a comparable analysis in live tissue has been lacking. Our STED images reveal a high degree of heterogeneity of spine sizes and morphologies, which agrees well with the previous electron microscopy work, but argues against morphological categorization schemes commonly used in the light microscopic literature [40][41][42] .…”
Section: Resolving Live Spine Morphologymentioning
confidence: 99%
“…In a similar analysis of the control material we failed to detect spine classes based on distribution histograms or scatterplots (Trommald and Hulleberg 1996). After LTP induction, neither distribution plots of head volume, minimal cross-sectional area, PSD area, nor spine length revealed any multimodality in the distribution plots (data not shown).…”
Section: Spine Dimensionsmentioning
confidence: 79%